2003
DOI: 10.1007/bf03033369
|View full text |Cite
|
Sign up to set email alerts
|

Brain sites of movement disorder: Genetic and environmental agents in neurodevelopmental perturbations

Abstract: In assessing and assimilating the neurodevelopmental basis of the so-called movement disorders it is probably useful to establish certain concepts that will modulate both the variation and selection of affliction, mechanisms-processes and diversity of disease states. Both genetic, developmental and degenerative aberrations are to be encompassed within such an approach, as well as all deviations from the necessary components of behaviour that are generally understood to incorporate "normal" functioning. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 371 publications
0
15
0
Order By: Relevance
“…These findings resemble the idiosyncratic bouts of repetitive behaviors noted in autism. Autism has been grouped with the movement disorders [109] and the contribution of seizures to these behaviors may be underappreciated [3] .…”
Section: Fig 6: Group Means (±Sem) For (A) Glutathione (Gsh) (B) Glmentioning
confidence: 99%
“…These findings resemble the idiosyncratic bouts of repetitive behaviors noted in autism. Autism has been grouped with the movement disorders [109] and the contribution of seizures to these behaviors may be underappreciated [3] .…”
Section: Fig 6: Group Means (±Sem) For (A) Glutathione (Gsh) (B) Glmentioning
confidence: 99%
“…The pathophysiology of the disorder remains unresolved, with a complex interaction of genetic, environmental and neurophysiological factors (cf. Rapport et al, 2000;Palomo et al, 2003). The genetic factor contributing to ADHD is substantial (e.g., Fisher et al, 2002;Smalley et al, 2002), reflecting associations with siblings , fathers (Frick et al, 1995) and mothers (Schacher and Wachsmuth, 1990;Faraone et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…Although the issue of animal models useful to a better understanding of ADHD is well-documented (cf. Davids et al, 2003;Palomo et al, 2003;Panksepp et al, 2003), the present study will present an alternative conceptualization of the putative neurodevelopmental 'accidents' implicated in the disorder, i.e., those involving the role of glutamate in development of brain systems.…”
Section: Introductionmentioning
confidence: 99%
“…Following the maturation of certain neural reflexes and motor coordination may give us an insight into the neurodevelopment of prenatally stressed animals. It has been shown that reflex ontogeny in rodents is influenced by several factors such as undernutrition, maternal care, toxic agents, environmental enrichment, genetic background [22][23][24][25][26][27][28][29][30]. We have previously described that perinatal hypoxic and toxic injuries remarkably delay the neurobehavioral development but 3-hr-long maternal separation induces only slight changes [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%